2018
DOI: 10.1136/bmjopen-2017-020892
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of barriers and enablers to South Asian women’s attendance for asymptomatic screening of breast and cervical cancers in emigrant countries

Abstract: ObjectivesThe aim of this review was to identify the cultural, social, structural and behavioural factors that influence asymptomatic breast and cervical cancer screening attendance in South Asian populations, in order to improve uptake and propose priorities for further research.DesignA systematic review of the literature for inductive, comparative, prospective and intervention studies. We searched the following databases: MEDLINE/In-Process, Web of Science, EMBASE, SCOPUS, CENTRAL, CDSR, CINAHL, PsycINFO and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 70 publications
2
41
1
Order By: Relevance
“…Consistent with the findings of the past research,[16] our study demonstrated a considerably low cancer screening uptake rate among South Asians, with atmost 36.9% of the population reported to have previously undertaken one particular cancer screening test. Such data demonstrated an urgent need for strategies that can effectively raise the awareness of local South Asians of the importance of screening in cancer prevention.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with the findings of the past research,[16] our study demonstrated a considerably low cancer screening uptake rate among South Asians, with atmost 36.9% of the population reported to have previously undertaken one particular cancer screening test. Such data demonstrated an urgent need for strategies that can effectively raise the awareness of local South Asians of the importance of screening in cancer prevention.…”
Section: Discussionsupporting
confidence: 92%
“…The systematic reviews had a broad geographic perspective (supplementary Appendix C), with some of them aiming to identify an evidence relevant for either specific countries (USA, the UK, France, Canada, or Japan), 13 20 geographic regions, 1 or populations by income or ethnicity. 21 24 Most of the reviews focused on interventions to improve participation rate (14) or behaviour of screened population and associated factors (12). The majority of reviews were publicly funded and no reviews reported a private source of funding (supplementary Appendix C).…”
Section: Resultsmentioning
confidence: 99%
“…This problem is not unique to refugees resettled in Australia, similar patterns of sub‐optimal screening behaviour are also found in other refugee and migrant women, particularly from South Asian populations, in other high‐income countries. Poor knowledge, cultural norms, practices and beliefs inhibit the uptake of cancer screening …”
Section: Introductionmentioning
confidence: 99%